The Effect of Position Promotion, Work Experience, and Mutation on Employee Performance Through Career Development as an Intervening Variable in the Situbondo Regency Government - Denny Chandra Irwana; Nursaid Nursaid; Ni Nyoman Putu Martini (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
In the midst of the challenges of stagnation of the performance of ASN employees in Situbondo Regency, such as punctuality of service and community satisfaction that are not optimal, this study examines the influence of position promotion, work experience, and mutation on employee performance through career development as an intervening variable in the Situbondo Regency Government. The purpose of the study was to analyze the direct and indirect influence of these three independent variables on employee performance, with a focus on career development mediation to provide recommendations for public sector human resource management. The quantitative research method uses PLS-SEM with WarpPLS on a sample of selected employees through purposive sampling from the population of experienced civil servants with structural positions, primary data from the Likert questionnaire, as well as descriptive analysis and hypothesis tests of direct and indirect pathways. The results showed that promotion had a significant positive effect on career development and employee performance, as well as work experience and mutation for both; Career development has a positive effect on performance, with significant partial mediating effects on all three pathways as well as a strong structural model. Research contributions include new mediation models for local government human resources policies, practical recommendations such as post-promotion individual development programs and mutation mentoring, as well as theoretical foundations for follow-up studies integrating moderation such as organizational commitment to optimize ASN performance